Effects of a low and a high dietary LA/ALA ratio on long-chain PUFA concentrations in red blood cells. Issue 9 (13th August 2018) - Greupner, Theresa; Kutzner, Laura; Pagenkopf, Svenja; Kohrs, Heike; Hahn, Andreas; Schebb, Nils Helge; Schuchardt, Jan Philipp
Abstract : There is a debate about the optimal dietary ratio of LA and ALA to promote an efficient conversion of ALA to EPA and DHA, which have implications for human health. Abstract : There is a debate about the optimal dietary ratio of the parent n6 fatty acid linoleic acid (LA) and n3 fatty acid alpha-linolenic acid (ALA) to promote an efficient conversion of ALA to EPA and DHA, which have implications for human health. The aim of the present study was to compare the effects of a low-LA/high-ALA (lo LA/hi ALA) diet with a high-LA/low-ALA (hi LA/lo ALA) diet on fatty acid concentrations in red blood cells (RBCs). Fifteen omnivore healthy men (mean age 26.1 ± 4.5 years) with a low initial EPA/DHA status (sum (∑) EPA + DHA% of total fatty acids in RBC at baseline: 4.03 ± 0.17) received both diets for two weeks with a nine-week wash-out phase in between. Fatty acid intake of the subjects was tightly controlled. Concentrations [μg mL −1 ] and relative amounts [% of total fatty acids] of fatty acids in RBCs were analyzed at baseline (day 0), day 7 and 14 by means of GC-FID. The dietary LA/ALA ratios were 0.56 ± 0.27 : 1 and 25.6 ± 2.41 : 1 and led to significantly different changes of ALA, LA, EPA and ∑EPA + DHA concentrations in RBCs. In the course of thelo LA/hi ALA diet ALA and EPA concentrations and relative amounts of ∑EPA + DHA increased, whereas LA concentrations decreased. The DHA concentration was unaffected. Thehi LA/lo ALA diet led to slightly decreased EPA concentrations, while all other fatty acid concentrations remained constant. Compared to our previous study, where we simply increased the ALA intake, our results show that ALA supplementation combined with a reduced LA intake (lo LA/hi ALA diet) more efficiently enhanced EPA blood concentrations. The absence of changes in the PUFA pattern in consequence of a LA/ALA ratio of 25.6 ± 2.41 : 1 suggests that the high LA/ALA ratio of the Western diet already leads to a saturation and a further increase of the ratio does not affect the PUFA pattern.